Motivasi Pengembangan Bisnis Perangkat Lunak Opensource - Kalalo, Henry (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
What drives companies with large proprietary software portfolios to invest hundreds of millions of dollars in to Open Source Society project? This paper tries to answer this question by dividing the Open Source Society project into clusters and examining the vendors motivation and contribution for each clusters. The paper find out that the motivation of the contribution are more. economically motivated to invest in open source society project that can serve as a complimentary asset to vendors ' core, proprietary business.